Quality function deployment: a comprehensive literature review. (22nd August 2008) - Sharma, J.R.; Rawani, A.M.; Barahate, Milind
In the past few years, various quality standards and quality systems have been attempted for the improvement of the products and services in our lives. One such quality tool which has the ability to generate creative and novel solutions is Quality Function Deployment (QFD). This paper presents a detailed literature review on the topic and application of QFD. This literature review is based on a reference bank of more than 400 QFDs and its allied publications, organisations, software, tools and web sources. The literature review is extended with thorough descriptions of the adopted methodologies, exemplified with an elaborate and categorical application analysis of its varied functional areas, namely, primary, secondary and tertiary fields, industrial, non-industrial and service applications and methodological progressions. The paper concludes with some of the insights gained from a large number of research papers, publications and other available literature.